Callose Synthesis Suppresses Cell Death Induced by Low-Calcium Conditions in Leaves. Issue 4 (5th February 2020) - Shikanai, Yusuke; Yoshida, Ryosuke; Hirano, Tomoko; Enomoto, Yusuke; Li, Baohai; Asada, Mayu; Yamagami, Mutsumi; Yamaguchi, Katsushi; Shigenobu, Shuji; Tabata, Ryo; Sawa, Shinichiro; Okada, Hiroki; et al.
Abstract : Callose is required for the suppression of cell death and necrosis induced by calcium deficiency. Abstract: Despite the importance of preventing calcium (Ca) deficiency disorders in agriculture, knowledge of the molecular mechanisms underlying plant adaptations to low-Ca conditions is limited. In this study, we provide evidence for a crucial involvement of callose synthesis in the survival of Arabidopsis ( Arabidopsis thaliana ) under low-Ca conditions. A mutant sensitive to low-Ca conditions, low calcium sensitive3 ( lcs3 ), exhibited high levels of cell death in emerging leaves and had defects in its expanding true leaves under low-Ca conditions. Further analyses showed that the causal mutation was located in a putative β-1, 3-glucan (callose) synthase gene, GLUCAN SYNTHASE-LIKE10 ( GSL10 ). Yeast complementation assay results showed that GSL10 encodes a functional callose synthase. Ectopic callose significantly accumulated in wild-type plants under low-Ca conditions, but at a low level in lcs3 . The low-Ca sensitivity of lcs3 was phenocopied by the application of callose synthase inhibitors in wild-type plants, which resulted in leaf expansion failure, cell death, and reduced ectopic callose levels under low-Ca conditions. Transcriptome analyses showed that the expression of genes related to cell wall and defense responses was altered in both wild-type plants under low-Ca conditions and in lcs3 under normal-Ca conditions, suggesting that GSL10 is required for the alleviation of both cell wall damage and defense responses caused by low Ca levels. These results suggest that callose synthesis is essential for the prevention of cell death under low-Ca conditions and plays a key role in plants' survival strategies under low-Ca conditions.